Drinking water, the most essential and not replaceable foodstuff - legal situation and assessment - Frimmel, Fritz H. (Acta Biologica Szegediensis, 2006)
The availability of water on the globe shows great regional differences. Due to the vital importance of water, quality criteria have been developed for its human consumption. In Europe the Water Directive gives the frame for national legislation concerning public water supply. Lists with parameters and highest acceptable concentrations are given as well as control and management principles to guarantee the health supporting function of water. The occurrence of different pollutants like pathogenic microorganisms, pesticides, pharmaceuticals, heavy metals and persistent organic chemicals clearly shows that water has to be treated before usage. Basis for this is a positive list of compounds including impurities and allowed amounts of added substances as well as remaining concentrations after separation. One of the highest objectives is to come to a sustainable water management. Green production, ecological product design, and consumer information are promising aspects to reach that goal.